Rôle de la cueillette, la pêche et la chasse dans l’alimentation au Laos - Florence Strigler (Revue d'ethnoécologie)
There are 6 million inhabitants in Laos, 80% of whom live in rural areas. Together with rice, which is their staple diet, Laotians consume a great variety of vegetable and animal products, obtained through gathering, fishing, and hunting. Those natural resources enable them to vary their food intake, but also to complement it during the periods of the year when their crops are insufficient. Within the current context of economic transition and new farming practices, the availability and accessibility of those resources are affected.